2016
DOI: 10.1055/s-0042-106975
|View full text |Cite
|
Sign up to set email alerts
|

Digital Planning Software Fails to Reflect Stem Torsion on Plain Radiographs after Total Hip Arthroplasty

Abstract: Purpose: The purpose of this study was to evaluate the validity of commercially available planning software on plain radiographs after THA compared to CT scans as the gold standard. Patients and Methods: In a prospective clinical study, anteroposterior (AP) radiographs and three-dimensional CT scans (3D-CT) were obtained for 121 patients, who underwent minimally invasive, cementless THA with a straight tapered stem, in a lateral decubitus position. For measuring SV, we used digital planning software (TraumaCa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…25 Conventional imaging is not sufficient to accurately predict postoperative prosthetic anteversion. 26 As the cost of a CT scan continues to decrease, the clinical advantages of having a more precise 3-dimensional plan, along with savings obtained from accurate sizing, might offset the initial costs of the preoperative CT. The radiation dose associated with the CT scan required for THR planning averages only 2.8mSv.…”
Section: Discussionmentioning
confidence: 99%
“…25 Conventional imaging is not sufficient to accurately predict postoperative prosthetic anteversion. 26 As the cost of a CT scan continues to decrease, the clinical advantages of having a more precise 3-dimensional plan, along with savings obtained from accurate sizing, might offset the initial costs of the preoperative CT. The radiation dose associated with the CT scan required for THR planning averages only 2.8mSv.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, angles of acetabular component position and measurement of leg length using the new software tool were as accurate as of the two widely accepted reference software platforms. When compared relative to a clinically relevant threshold of ±5° or ±5 mm [ 24 ], proportional analyses revealed that for acetabular component orientation and leg length, 100% of the new software’s measurements fell within this threshold, with the only exception being inclination relative to the SRV, which saw 99.3% of inclination measurements fall within 5° of the reference value. Further, 94.4% of anteversion and 95.8% of inclination measurements were within 1° of the PRV measurements, while 90.2% of inclination measurements were within 1° of the SRV measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Through considerable improvements in diagnostic software and hardware, MARS (metal artefact reduction sequence) MRI has recently been shown to present good sensitivity and specificity to detect component loosening [18]. CT scans offer improved resolution and are useful in the analysis of focal osteolysis, deformities such as rotational abnormalities and improved digital planning capacities [19][20][21]. X-ray still present the first imaging step when loosening of hip prosthesis is suspected and present with a decent sensitivity and specificity but are not as specific/sensitive as MRI and CT [22].…”
Section: Discussionmentioning
confidence: 99%